Assessment Of Green HRM Practices and Their Effect On Employee Performance and Career Growth Of Young Talent In Hotels - Dyah Palupiningtyas; Krisnawati Setyaningrum Nugraheni; Aletta Dewi Maria; C Susmono Widagdo (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
This study aims to evaluate the implementation of Green Human Resource Management (GHRM) policies and their impact on the performance and career development of young talent in star-rated hotels in Semarang City that have adopted the Green Hotel concept. Using a qualitative approach and case study design, data were collected through semi-structured interviews with young employees, HR managers, and hotel management, as well as direct observation and document analysis. The results show that GHRM practices, such as recruitment and selection, training and development, performance appraisal, and employee involvement, have been implemented with varying levels of depth across these hotels. GHRM practices have been shown to positively impact the performance of young employees and open up career development opportunities. However, the effectiveness of GHRM implementation is influenced by various factors, such as management commitment, policy clarity, training quality, resource availability, organizational culture, and communication and feedback systems. The findings of this study contribute theoretically to the GHRM and strategic HRM literature and provide practical implications for HR management in the hospitality industry in supporting sustainable tourism development. These results highlight the importance of synergy between GHRM policies and managerial commitment in creating a work environment that supports sustainability and employee career development, particularly for young talent who have the potential to become future leaders.